Characterization of a metazoan ADA acetyltransferase complex. Issue 7 (31st January 2019) - Soffers, Jelly H M; Li, Xuanying; Saraf, Anita; Seidel, Christopher W; Florens, Laurence; Washburn, Michael P; Abmayr, Susan M; Workman, Jerry L
Abstract: The Gcn5 acetyltransferase functions in multiple acetyltransferase complexes in yeast and metazoans. Yeast Gcn5 is part of the large SAGA (Spt-Ada-Gcn5 acetyltransferase) complex and a smaller ADA acetyltransferase complex. In flies and mammals, Gcn5 (and its homolog pCAF) is part of various versions of the SAGA complex and another large acetyltransferase complex, ATAC (Ada2A containing acetyltransferase complex). However, a complex analogous to the small ADA complex in yeast has never been described in metazoans. Previous studies in Drosophila hinted at the existence of a small complex which contains Ada2b, a partner of Gcn5 in the SAGA complex. Here we have purified and characterized the composition of this complex and show that it is composed of Gcn5, Ada2b, Ada3 and Sgf29. Hence, we have named it the metazoan 'ADA complex'. We demonstrate that the fly ADA complex has histone acetylation activity on histones and nucleosome substrates. Moreover, ChIP-Sequencing experiments identified Ada2b peaks that overlap with another SAGA subunit, Spt3, as well as Ada2b peaks that do not overlap with Spt3 suggesting that the ADA complex binds chromosomal sites independent of the larger SAGA complex.